FORMULASI SEDIAAN SALEP EKSTRAK ETANOL DAUN ALPUKAT (Persea americana Mill.) SEBAGAI ANTIACNE - Yulistia Budianti Soemarie; Tri Astuti; Nur Rochmah (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2016)
Currently, the development of acne drugs (antiacne) use many natural materials because the natural materials can minimize the side effect if compared with synthetic chemicals drugs. Acne can caused by propionibacterium acnes, staphylococcus epidermis and staphylococcus aureu. One of plants that can be used for acne treatment is leaves of Avocado (Persea americana Mill). The aim of this study was to know whether the ethanol extract of leaves of avocado (Persea americana Mill.) can be made into an ointment preparations that fulfill the requirements. Sample in this research was extract of avocado leaves which used maceration method. The ointment formulations were made into some variation concentrations of PEG 400 and PEG 4000: Formula I (30%:70%); Formula II (50%:50%) and Formula III (70%:30%). The results show that the ointment of avocado leaves which fulfilled the requirements of physical properties is formula III with concentration of PEG 400 70 % and PEG 4000 30 %